Effects of soil properties to corrosion of underground pipelines: a review - S.R.A. Saupi; Muhammad Azwadi Sulaiman; Mohamad Najmi Masri (Universiti Malaysia Kelantan, 2015)
This review concentrates on corrosion properties that expose to soil environment. Forms of corrosion classified with respect to outward appearance and altered physical properties are uniform attack, galvanic corrosion, erosion corrosion, stress corrosion, crevice corrosion, pitting and inter-granular corrosion. A porous soil may retain moisture for a longer period for optimum aeration and indirectly increase the initial corrosion rate. External corrosion is corrosion attack upon the outside of the pipe soil medium and the most failure mechanisms experienced by buried steel pipelines. Many systems possibly in contact with soil have risk to be corroded such as storage tanks and pipelines.